Conformational change due to replacement of disulfide with selenosulfide and diselenide in dipeptide vicinal cysteine loop. (April 2022) - Reddy, K. Kasi Amarnath; Sahoo, Deepak Kumar; Moi, Smriti; Gowd, Konkallu Hanumae
Abstract: Replacement of disulfide bridges with diselenide bridges is increasingly common to improve the stability, foldability, and structural refinement of the cysteine-rich polypeptides. Even though the global structural features are similar due to the replacement of disulfide with diselenide, the local conformational differences have been reported in a few polypeptides. The current report has used the constrained vicinal cysteine disulfide as the model to access the influence of the replacement of disulfides with diselenide on the local conformations. Using the density functional theory (DFT), structures of dipeptide vicinal loops are optimized by systematically replacing sulfur with selenium. Conformations of the disulfide/selenosulfide/diselenide were identified using the side-chain torsional angle χ1, χ2, χ3, χ2 ′, χ1 ′ and mapped to one of the possible 32 conformations of the cysteine disulfide. Further, the influence of the change of configuration of Cα-atom of cysteine/selenocysteine from 'R′ to 'S′ configuration and peptide bond from cis to trans has also been accessed on the conformations of dipeptide vicinal loops. The results indicate that diselenide/selenosulfide explores additional conformational space apart from accommodating the conformations observed in the vicinal disulfide which is more amplified in the heterochiral system. Differences have been observed at the internal coordinates of the optimized structures of dipeptide vicinal disulfide, selenosulfide, and diselenide. The change in free energy (ΔG), spin density (Δs(r)), and electron density (Δρ(r)) was also calculated due to the replacement of disulfide with selenosulfide/diselenide. Conformational analysis of disulfides and that of the replaced diselenides in the crystal structures of the proteins retrieved from PDB have also indicated the retention as well as differences in the local conformations. The tendency of the diselenide loop to explore the additional conformational space may prompt for the local conformational differences in the corresponding disulfide to diselenide replaced polypeptides. Graphical Abstract: ga1 Highlights: The local conformations of disulfide and diselenide were compared in dipeptide vicinal loop. Conformational preferences were evaluated and identified using density functional theory. Diselenides explores additional conformational space apart from exploring that of disulfides. In protein crystals, conformations of diselenide retained/changed compared to disulfides. Local conformational difference may occur during replacement of disulfide with diselenide.